Le tourisme dans les environnements littoraux et insulaires : permanences, limites et perspectives - Olivier Dehoorne; Caroline Tafani (Études Caribéennes)
Coastlines and islands are particularly affected by the development of tourism worldwide. Between "desired costal" and "fantasy Islands", these coveted spaces, with both their tangible and intangible dimensions, are opening to tourism. Attracted by the economic opportunities they so desperately need, and more or less aware of their comparative advantages and limitations, they deliver the most vulnerable preserved resources, the most vulnerable, which are the subject of complex relationships and issues.